An ergonomics study on hand parameters for intuitive controls and better precision - Shikha Singh, Nidhi Sharma, S. K. Jain, Sonika Sharma (South Eastern European Journal of Public Health, 2025)
Introduction:The ergonomic research is useful for redesigning tools that increase healthcare providers' productivity. surgeons may experience pain, exhaustion, and injuries as a result of ergonomic difficulties in the operating room, which might have a detrimental effect on their patient outcomes and performance. Small female hands find it more difficult to use devices designed for bigger male hands, which reduces their level of efficiency and increases their risk of musculoskeletal diseases (MSDs). The purpose of this research is to improve efficiency and comfort in surgery by designing surgical tools based on an anthropometric analysis of hand parameters. Methods:335 Indian healthcare professionals-168 men and 167 women-were the subjects of the research. Every participant's dominant hand was used to assess a range of anthropometric and biomechanical characteristics, such as length of the hand, width, and span of the hand, wrist circumference was measured by using a measuring tape and handgrip strength with a Jamar dynamometer. Results:Using SPSS version 25, the t-test was used to analyze the data and reveal that there were significant differences (p= < 0.05) in the hand dimensions and strength assessments between the both genders. These results highlight the need for surgical tools that are configurable and adaptive in order to meet the ergonomic requirements of all users, especially in light of the issue of instruments that are predominantly made for bigger male hands. Conclusion:This research emphasizes how important it is to use anthropometric data when designing surgical instruments in order to enhance surgeons' occupational health and improve surgical results. The long-term advantages of these revised devices and their effect on surgical efficiency and safety will be the primary fields of future study.